The bioinformatics analysis of the clinicopathological and prognostic significances of REG4 mRNA in gynecological cancers - Cong-yu Zhang; Li Zhang; Zi-mo Wang; Dong-hui Ren; Hua-chuan Zheng (Taylor & Francis Group, 2023)
To clarify the clinicopathological importance of REG4 mRNA expression, we used GEO, TCGA, xiantao, UALCAN, and Kaplan-Meier plotter for a bioinformatics analysis in breast, cervical, endometrial and ovarian cancers. Compared to normal tissues, REG4 expression was found to be upregulated in breast, cervical, endometrial, and ovarian cancers (p < 0.05). Breast cancer had a higher level of REG4 methylation than normal tissues (p < 0.05), which was negatively correlated with its mRNA expression. REG4 expression was positively correlated with oestrogen and progesterone receptor expression, and aggressiveness of PAM50 classification of breast cancer patients (p < 0.05). Breast infiltrating lobular carcinomas expressed more REG4 than ductal carcinomas (p < 0.05). The REG4-related signal pathways mainly included peptidase, keratinisation, brush border and digestion and so forth in gynecological cancers. Our results indicated that REG4 overexpression was associated with gynecological carcinogenesis and their histogenesis, and may be used as a marker for aggressive behaviour and prognosis of breast or cervical cancer.IMPACT STATEMENT What is already known on this subject? REG4 encodes a secretory c-type lectin and plays an essential role in inflammation, carcinogenesis, apoptotic and radiochemotherapeutic resistance. What do the results of this study add? As a standalone predictor, REG4 expression was positively correlated with progression-free survival. Expression of REG4 mRNA was positively associated with the T stage and adenosquamous cell carcinoma of cervical cancer. The top signal pathways related to REG4 included smell and chemical stimulus, peptidase, intermediate filament, and keratinisation in breast cancer; ligand-receptor interaction, metabolism of hormone, xenobiotic and retinol, peptidase, brush border and digestion in cervical and ovarian cancers; bile secretion, intermediate filament, chemical carcinogenesis, brush border and keratinisation in endometrial cancer. REG4 mRNA expression was positively correlated with DC cell infiltration in breast cancer, positively with Th17 cells, TFH, cytotoxic cells and T cells in cervical and endometrial cancers, and negatively with DC cell infiltration, cytotoxic cells and T cells in ovarian cancer. The top hub genes mainly included small proline rich protein 2B in breast cancer; fibrinogens and apoproteins in cervical, endometrial and ovarian cancers. What are the implications of these finding for clinical practice and/or further research? Our study has showed that REG4 mRNA expression is a potential biomarker or therapeutic target for gynaecologic cancers.